Improvement of the value and anisotropy of critical current density in GdBa2Cu3O7-δ coated conductors with self-assembled 3-dimensional BaZrO3 nanostructure. (September 2021) - Gantepogu, Chandra Shekar; Yang, Chia-Ming; Ganesan, Peramaiyan; Chen, In-Gann; Wang, Ming-Jye; MacManus-Driscoll, Judith; Moon, Seung-Hyun; Wang, Connie; Wu, Maw-Kuen
Abstract: In this study, we investigate the GdBa2 Cu3 O7– x (Gd123) films with several types of self-assembled BaZrO3 (BZO) nanostructure on the ion-beam-assisted deposited MgO substrate (I-BAD) buffered with (La, Sr)MnO3 . With additional in-situ annealing between the BZO-doped Gd123 and BZO bilayer, the BZO-doped-Gd123/BZO multilayer sample reveals a three-dimensional (3D) BZO nanostructure network in the Gd123 matrix, which significantly enhances the critical current density J C and flux pinning force ( F p ) under high magnetic fields both along the c -axis and ab -plane. The studies on the resistance near transition temperature and the flux dynamic demonstrate that the flux pinning in the tape with a 3D BZO nanostructure network is more 3D-like. With the 3D BZO nanostructure network, our superconductor-coated conductor's performance in J C (extracted from magnetic and transport data) and angular dependence at high magnetic field is better than the existing reported results, and it could be further improved by optimizing BZO nanostructure parameters. Graphical abstract: Image 1 Highlights: Gd123-BZO nanostructured films were grown by the PLD under novel heat treatment. 3D BZO nanostructure acts as the effective vortex pinning centers at high fields. JC and FP are significantly enhanced under high magnetic fields.